2022
DOI: 10.3390/foods11020194
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Colon Cancer Activity of Novel Peptides Isolated from In Vitro Digestion of Quinoa Protein in Caco-2 Cells

Abstract: Quinoa peptides are the bioactive components obtained from quinoa protein digestion, which have been proved to possess various biological activities. However, there are few studies on the anticancer activity of quinoa peptides, and the mechanism has not been clarified. In this study, the novel quinoa peptides were obtained from quinoa protein hydrolysate and identified by liquid chromatography–tandem mass spectrometry (LC–MS/MS). The anticancer activity of these peptides was predicted by PeptideRanker and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Quinoa oil nanoemulsion administration showed marked improvement, manifested by a reduction in epithelial cell proliferation. This is in agreement with a recent study that con rms the anti-proliferative role of quinoa peptide in obstructing colon cancer cell proliferation [43]. Also, a study demonstrated that quinoa seed oil inhibits the growth of HCT 116 cells by inducing apoptosis, suggesting that it may be used as a functional food to prevent colon cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Quinoa oil nanoemulsion administration showed marked improvement, manifested by a reduction in epithelial cell proliferation. This is in agreement with a recent study that con rms the anti-proliferative role of quinoa peptide in obstructing colon cancer cell proliferation [43]. Also, a study demonstrated that quinoa seed oil inhibits the growth of HCT 116 cells by inducing apoptosis, suggesting that it may be used as a functional food to prevent colon cancer.…”
Section: Discussionsupporting
confidence: 92%
“…The same author also demonstrated that the antidiabetic effects of quinoa peptides were due to enzyme inhibition of α- amylase, α-glucosidase, and dipeptidyl peptidase IV. Guo et al [ 32 ] showed that quinoa peptides obtained through in vitro digestion exhibited antihypertensive effects in rats in the form of ACE inhibitory activity. Similar to quinoa, the peptides from raw and heat-treated amaranth seeds showed anticancer activity by apoptosis and cell growth inhibition when evaluated using breast cancer cell lines [ 33 ] and HT-29 colon cancer cells [ 34 ].…”
Section: Nutritional Significance and Health Benefits Of Ancient Grai...mentioning
confidence: 99%
“…These studies have revealed the remarkable potential of quinoa protein in generating bioactive peptides with multifunctional properties, including hypoglycemic, antihypertensive, antidiabetic, anti-colon cancer, anti-inflammatory, and antioxidant activities. [14][15][16][17] Lunasin, a 43-amino-acid peptide found in quinoa seeds, has been shown to inhibit nitric oxide (NO) and inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α) and interleukin-6 in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. 17 Additionally, chenopodin, another component of quinoa, has demonstrated the ability to decrease the expression levels of NF-κB and IL-8 in Caco-2 cells.…”
Section: Introductionmentioning
confidence: 99%